Effect of siRNA terminal mismatches on TRBP and Dicer binding and silencing efficacy - Kini, Hemant K. (2009)
To enhance silencing and avoid off-target effects, siRNAs are often designed with an intentional bias to ensure that the end of the siRNA that contains the guide strand 5′ end is less stably hybridized relative to the end containing the passenger strand 5′ end. One means by which this is accomplished is to introduce a terminal mismatch, typically by changing the passenger strand sequence to impair its hybridization with the guide strand 5′ end. However, there are conflicting reports about the influence of terminal mismatches on the silencing efficacy of siRNAs. Here, the silencing efficiency of siRNAs with a terminal mismatch generated either by altering the guide strand (at the 5′ end, nucleotide 1) or the passenger strand (nucleotide 19 from the 5′ end) was examined. Subsequently, we studied the relationship between the silencing efficiency of the siRNAs and their binding to the RNA-induced silencing complex loading complex proteins HIV transactivating response RNA-binding protein and Dicer in H1299 cytoplasmic extracts. Binding of siRNA and the transactivating response RNA-binding protein was significantly reduced by terminal mismatches, which largely agrees with the reduction in eventual silencing efficacy of the siRNAs. Single terminal mismatches led to a small increase in Dicer binding, as expected, but this did not lead to an improvement in silencing activity. These results demonstrate that introduction of mismatches to control siRNA asymmetry may not always improve target silencing, and that care should be taken when designing siRNAs using this technique.